Development of approaches for studying the biodistribution of a bicistronic therapeutic plasmid construct in the mouse body - S. S. Dzhauari; M. N. Karagyaur; V. Yu. Balabanyan; M. N. Skryabina; A. L. Primak; D. V. Stambolsky (Фармакокинетика и Фармакодинамика, 2022)
Relevance. The use of gene therapy drugs for the treatment of genetic diseases and stimulation of regeneration processes is lengthy and involves repeated injections, which may lead to increased dissemination of gene therapy constructs from the injection site and undesirable ectopic expression of growth factors encoded in them. Existing approaches to study the pharmacokinetics of a drug to assess the dissemination of a gene therapy drug from the site of administration are not applicable. Objective: to evaluate the suitability of the real-time PCR method for studying the biodistribution of a promising gene therapy drug in mice during a course of use. Methods. Male F1 CBA×C57/Black mice after nerve injury were injected with the test plasmid into the denervated tibial muscle after nerve injury, as well as after 4, 9 and 13 days at a dosage of 60 and 120 μg/mouse. After 7, 14, and 28 days, organ and tissue samples were removed, total DNA was isolated, and plasmid DNA content was assessed by real-time PCR. Results. We have shown that the studied genetic construct is able to disseminate from the injection site. We have found that the peak of dissemination for this construct in the organs and tissues of the mouse is reached 14–28 days after the end of the course application, while ectopic expression of growth factors is not observed in them. Conclusion. The proposed method is specific, highly sensitive, and linear over a wide range of concentrations. Thus, it can be recommended for studying the biodistribution of potential gene therapy drugs in the body of experimental animals as part of a preclinical studies complex.